Original paperContact hypersensitivity to selected cosmetic ingredients and other allergens among cosmeticians and students of cosmetology - Kacalak-Rzepka, Anna; Bielecka-Grzela, Stanisława; Różewicka-Czabańska, Monika; Maleszka, Romuald; Klimowicz, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Hypersensitivity to cosmetic ingredients is a significant clinical issue due to their common usage. Among the substances contained in cosmetics, contact allergy may be caused by fragrance additives, preservatives, vehicles and dyes. Aim : To assess the frequency of contact allergy to selected cosmetic ingredients and other allergens based on the results of patch tests carried out on cosmeticians and students of cosmetology. Material and methods : The distribution of allergies in this group was compared to that of the control group consisting of female volunteers in the same age period. Results and conclusions : The results of patch tests indicated that among cosmeticians and students of cosmetology, contact allergy occurred statistically significantly more often than in women not connected with this profession. The most common sensitizing allergen, regardless of the type of profession, was nickel. Among allergens occurring in cosmetic products, hypersensitivity to merthiolate and paraphenylenediamine was observed most frequently in the study group.